Sense of Coherence and Driver Stress in Ridesharing Drivers as Moderated by Community Affiliation - Grasiaswaty, Novika; Sadida, Nuri; Aliviary, Alexandra (Psychological Research on Urban Society, 2020)
The present research aimed to test whether community involvement moderates the relationship between sense of coherence (SOC) and driver stress among online ridesharing drivers. The study used a quantitative design to collect data via questionnaires. All 112 participants were male and chose online ridesharing as their primary occupation. Participants were assessed using the Work Sense of Coherence Scale and Driver Stress Scale, a subscale of Driving Behavior Inventory. Community involvement was measured with a close-ended question in the demographic section of the questionnaire, with dichotomous options provided (1 = community participation; 0 = no community participation). Collected data were analyzed using JASP to examine the moderating effect. The results of this study showed that community involvement moderates the relationship between SOC and driver stress in online ridesharing drivers.